Features of anthrax natural foci and Bacillus anthracis ecology - A. P. Rodionov; E. A. Artemeva; L. A. Melnikova; M. A. Kosarev; S. V. Ivanova (Ветеринария сегодня)
Anthrax remains a global problem, both for veterinary and human medicine, due to the wide spread of its soil foci throughout the world. The ability to sporulate is the main feature of Bacillus anthracis, which allows the pathogen to persist in the environment for a long time. Understanding the ecology of B. anthracis is essential for successful control of this infection. This review analyzes the data from the global literature, reflecting the modern understanding of the vital functions of the anthrax agent in various ecological niches. As a result of the work, it was revealed that many links in the chain of B. anthracis lifecycle in the abiotic environment remain poorly understood. A more in-depth study is required for issues related to the mechanisms, ways of living and evolution of the anthrax causative agent outside the animal body. A separate section of the review describes the problems of anthrax foci in soil. It is shown that today there are no effective and environmentally friendly methods and means of their elimination. In addition, the question of the expediency of their use remains open. According to some researchers, the increasingly emerging initiatives for the elimination or conservation of anthrax burial sites are not only useless, but also harmful, since they exclude the possibility of further predicting the risks associated with soil foci that surround livestock burial sites and cannot be decontaminated. The study and new approaches to solution of the highlighted issues will make a significant contribution to solving the global problem of protecting animals and people from this infection.